Can integrated skills tasks change students' learning strategies and materials?. Issue 3 (3rd July 2017) - Wei, Wei
Abstract : The use of integrated skills tasks in language tests has been debated for many years and international English test developers such as Educational Testing Service (ETS) and Pearson Tests of English (PTE) already use such tests to assess English as a foreign language (EFL) learners' language proficiency. Empirical research has rarely investigated the influence of the integrated skills task on test takers' preparation strategies. The study presented here set out to investigate the extent to which the introduction of integrated skills tasks may change students' test preparation strategies and the resources that they choose to use. The research focused on two integrated test types developed by PTE Academic: 'repeat-sentence' and 're-tell lecture', which assess both speaking and listening skills concurrently. Data on test-takers' strategies and resources were collected by using Oxford's (1990) Strategy Inventory for Language Learning (SILL). The findings indicated that the integrated skills test influenced participants in relation to both their choice of preparation strategies and the resources chosen. These choices seemed to vary in line with participants' awareness of different aspects of the new test. Thus, there appeared to be an association between participants' choices of learning strategies and resources and their awareness of which skills were being assessed and the nature of the audio input in the new formats. Finally, despite evidence that the new integrated skills test had some impact on participants' approaches to their language learning, this did not necessarily mean that the participants completely abandoned existing learning strategies and resources, in particular those appropriate to the previous test formats.